Insights into permeability of rejuvenator in old asphalt based on permeation theory: Permeation behaviors and micro characteristics. (28th March 2022) - Fang, Ying; Zhang, Zhengqi; Shi, Jierong; Yang, Xinhong; Li, Xinjun
Highlights: The higher permeation temperature or longer time contributed the permeation effect. The permeability of mineral oil rejuvenator in aged asphalt was stronger than that of bio-rejuvenator. Thinner aged asphalt layer made the rejuvenator more easily permeate. Similar micro morphological and mechanical properties appeared at different layers of L-type RFLs. L-type rejuvenator contained lower carbonyl and exhibited better permeability. Abstract: Aiming to analyze the permeation behaviors and micro characteristics of rejuvenator in old asphalt, the rejuvenation fusion layer (RFL) of rejuvenator and old asphalt was first fabricated by permeation test. Then, the viscosity of RFLs was analyzed and its several influencing factors were explored via conducting the rotational viscosity test. On this basis, coupled with Fick's law and composite material theory, the permeability coefficient ( D ) of rejuvenator in old asphalt was calculated and the influencing factors were investigated. Lastly, the micro-phase morphology, mechanical and chemical characteristics of RFL were analyzed via the AFM and FTIR tests. Results showed that the permeability of rejuvenator in old asphalt depended on permeation temperature, permeation time, rejuvenator type and asphalt layer thickness. The higher permeation temperature or longer time contributed to the permeation effect of rejuvenator in old asphalt. Moreover, based on the results, the mixing temperature should not be less than 150 °C and the mixing time should be about 12 s ∼ 18 s for the uniform mixing of RAP and rejuvenator in actual thermal rejuvenation engineering. The permeability of mineral oil rejuvenator in aged asphalt was stronger than that of bio-rejuvenator, and thinner aged asphalt layer made the rejuvenator more easily permeate. Further, the sampling layer exhibited the most remarkable influence on the permeability of rejuvenator in old asphalt, followed by rejuvenator type, permeation time and permeation temperature. The AFM test confirmed that the permeation effect of mineral oil rejuvenator in aged asphalt was superior to that of bio-rejuvenator from the micro perspective, and that under the permeation conditions of 130 °C and 6 h, the mineral oil rejuvenator can fully fuse with aged asphalt and show similar morphological characteristics ("bee" size and quantity) at different layers of RFLs. Further, the mineral oil rejuvenator greatly enhanced the micro mechanical properties of aged asphalt, demonstrating a favorable rejuvenation effect. FTIR test manifested that the functional group composition of the L-type rejuvenator was similar to that of the original asphalt, and that the L-type rejuvenator contained lower carbonyl contents compared to B-type and H-type rejuvenators and exhibited better permeability and rejuvenation effect.